Nonlinear parametric scattering of exciton polaritons in perovskite microcavities - Wu, Jinqi (2022)
Comparing with pure photons, higher nonlinearity in polariton systems has been exploited in various proof-of-principle demonstrations of efficient optical devices based on the parametric scattering effect. However, most of them demand cryogenic temperatures limited by the small exciton binding energy of traditional semiconductors or exhibit weak nonlinearity resulting from Frenkel excitons. Lead halide perovskites, possessing both a large binding energy and a strong polariton interaction, emerge as ideal platforms to explore nonlinear polariton physics toward room temperature operation. Here, we report the first observation of nonlinear parametric scattering in a lead halide perovskite microcavity with multiple polariton branches at room temperature. Driven by the scattering source from condensation in one polariton branch, correlated polariton pairs are obtained at high k states in an adjacent branch. Our results strongly advocate the ability to reach the nonlinear regime essential for perovskite polaritonics working at room temperature.